The impact of debt financing on the financial performance of small and medium enterprises - Ankunda Zabandra Rynah (Uganda Christian University, 2024)
This research was intended to evaluate the impact of debt financing to the small and medium enterprises on small and medium enterprises in Mukono town in Mukono district. The study objectives included; To assess the role of short term financing on the financial performance of small and medium enterprises in Mukono town, to examine the role of long term financing on the financial performance of small and medium enterprises in Mukono town and to determine the relationship between debt financing and financial performance of small and medium enterprises in Mukono town. The study used a cross-sectional, non-experimental and descriptive survey design. The study had a population of 95 registered SMEs from Mukono town. Simple random sampling method was used to choose the sample size which was 77 SMEs. A questionnaire was used for data collection in this study. Primary data and secondary data was used in the study. Data analysis was done using SPSS version 20 for the collected data. Basing on the study findings, the response rate was 81.8%. This study found out that short term financing and long term financing positively influence the financial performance of small and medium enterprises. It also found out that the relationship between debt financing and financial performance of small and medium enterprises was a strong relationship (0.926) basing on the correlation and the regression analysis tool. In conclusion, debt financing positively influences the financial performance of small and medium enterprises in Mukono town in Mukono district. The study recommends that small and medium enterprises should seek financial literacy mainly on debt financing and also policy holders could make a convenient for businesses to acquire loans such as loosening policies concerning SMEs so as to enhance their financial performance.